Relation between Helicoverpa armigera (Hubner) (Lepidoptera/Noctuidae) mortality and entomopathogenic fungi persistence in soybean leaflets - de Souza, Tamires Doroteo [UNESP]; Fernandes, Fabricio Oliveira [UNESP]; Sanches, Ariadne Costa [UNESP]; do Nascimento, Joacir [UNESP]; Pinto, Antonio Alves [UNESP]; Polanczyk, Ricardo Antônio [UNESP] (Springer Nature, 2022)
​Background: Entomopathogenic fungi have low persistence in the field because of UV light, high temperatures and low humidity. Thus, this study's objective was to correlate the persistence of Beauveria bassiana and Metarhizium anisopliae in soybean leaf by measuring the mortality and sub-lethal effects of Helicoverpa armigera (Hubner) (Lepidoptera/Noctuidae). In the 2017–2018 and 2019–2020 soybean seasons, the experiments were conducted on plots subdivided in a completely randomized design. After spraying each plot with the fungal, either B. bassiana or M. anisopliae, leaves were collected hourly for 8 h after application and transferred to the laboratory. The local air temperature was recorded each time. For persistence assessment, the fungal suspension was prepared from the leaf disks; thereafter, 150 µl of the suspension was removed and poured into a plate. After 72 h of inoculation, colony-forming units (CFUs) were counted. For the mortality test, the leaf disks were placed individually in pots and offered to second instar larvae of H. armigera. The surviving larvae were evaluated for sub-lethal effects and biological parameters. Results: Beauveria bassiana was more persistent than M. anisopliae, which persisted for 3 h in the first year and 5 h in the second year when temperatures were milder; B. bassiana persisted throughout the evaluation period (8 h). The mortality of H. armigera decreased with an increase in the time since application fungal suspension, presenting a range of 86–30% for B. bassiana and 78–4.2% for M. anisopliae. Conclusion: Assessments of sublethal effects showed an inverse correlation between CFUs and parameters such as fertility and weight.
Keywords: Fungal control; Green Muscardine; Helicoverpa armigera; Sublethal effects; Virulence; White Muscardine